DETERMINATION OF POTENTIAL HYDROCARBON AND TECTONOSTRATIGRAPHY ANALYSIS BASED ON 2D SEISMIC IN PADAMARANG SUB-BASIN, BONE BASIN, SOUTH PART OF SULAWESI - Haqiqie, Fauzan Aditya; Sunardi, Edy; Ilmi, Nisa Nurul; Ginting, Agus Santa (Faculty of Geological Engineering, Universitas Padjadjaran, 2018)
Sulawesi is a main island in Indonesia that has a complex geological setting. This complexity is caused by assemblage of 3 major plates called as triple junction. Repercussions of these plates assemblage is emerging many basins in Sulawesi area, Bone Basin is one of it. Bone Gulf is a prospect basin for petroleum exploration. Bone Gulf is a frontier area for hydrocarbon exploration. In order to understand and to determinate lead of a frontier area, Seismic interpretation through 2D seismic data is required. 2D seismic interpretation in this area of study using tectonostratographic approach. This study could be a reference and recommendation for further hydrocarbon exploration in this area. This study shows a result that in Bone Basin has 3 main sub-basins (Padamarang, North Kabaena, and South Kabaena) separated by basement highs and this research focused in Padamarang Sub-basin. There are 4 Tectonostratigraphic units in Padamarang Sub-basin, these are include basement (Unit X), Early Rifting (Unit A), Rifting (Unit B), Post Rift (Unit C), dan Post Rift (Seabed/ Unit D & E). There are 2 lead located in Late Miocene Carbonate buildups (represents in seismic section as mounded seismic horizon) showed in BN07-06 and BN07-07 seismic cross section on Padamarang Sub-basin.